Machine Learning-Based Approach for EV Charging Behavior - Shahriar, Sakib (2021)
A Master of Science thesis in Computer Engineering by Sakib Shahriar entitled, “Machine Learning-Based Approach for EV Charging Behavior”, submitted in April 2021. Thesis advisor is Dr. Abdulrahman Al-Ali and thesis co-advisor is Dr. Ahmed Osman-Ahmed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).